Strong non-repudiation certificateless scheme with an aggregate signature in vehicular ad-hoc network - Abdelkrim Imghoure; Ahmed El-Yahyaoui; Fouzia Omary (Franklin Open)
In Vehicular Ad-Hoc Networks (VANETs), a Certificateless Aggregate Signature (CLAS) scheme with a conditional anonymity authentication meets both anonymity and security requirements. This scheme enables a roadside unit to aggregate multiple signatures during Vehicle-to-Infrastructure communications and send the aggregate signature to other RSUs and a traffic control center. However, according to Girault's classification of trust levels (TLs) [1], the existing CLAS schemes only achieve TL 2. At this level, a malicious Trusted Authority (TA) or vehicle can impersonate a legitimate vehicle by launching a public key replacement attack during the authentication process. Consequently, the existing research does not provide strong non-repudiation, as it cannot be proven whether the authority or the vehicle has replaced the original public key. In this study, a new CLAS scheme is designed that achieves TL 3 using asymmetric pairing with a type-2 sitting and the hashing technique of Al-Riyami and Paterson [2]. The results demonstrate that the proposed CLAS scheme offers strong non-repudiation and effectively prevents a public key replacement attack. A security proof is carried out and demonstrates that our scheme achieves Existential Unforgeability under Chosen Message Attack (EUF-CMA) security in the random oracle. Furthermore, the simulation outcomes demonstrate that the proposed scheme outperforms the existing schemes and allows to save communication bandwidth during V2I communications in VANET [3].